2017
DOI: 10.18632/oncotarget.17059
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-related microRNA-145-5p enhances the effects of pheophorbide a-based photodynamic therapy in oral cancer

Abstract: MicroRNAs (miRNAs) regulate key biological processes, and their aberrant expression has been related to cancer development. Photodynamic therapy (PDT) has emerged as one of the most promising modalities for cancer treatment. However, the application of PDT has been limited to superficially localized human cancerous and precancerous lesions. To increase the usefulness of both PDT and miRNAs in cancer therapy, this study investigated whether apoptosis-related miRNA expression is influenced by PDT in oral cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…MiR-32-5p was significantly decreased in fatty acids-treated human colorectal adenocarcinoma cells accompanied by a decrease in BCL-2 and BCL2L11 expression [ 24 ]. In addition, photodynamic therapy strongly down-regulated the expression miR-32-5p in oral cancer cells, but its roles in the therapeutic effect of photodynamic therapy are unknown [ 25 ]. Our results firstly identified that miR-32-5p was increased in PC tissues and cells, and was associated with the migration and invasion of PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-32-5p was significantly decreased in fatty acids-treated human colorectal adenocarcinoma cells accompanied by a decrease in BCL-2 and BCL2L11 expression [ 24 ]. In addition, photodynamic therapy strongly down-regulated the expression miR-32-5p in oral cancer cells, but its roles in the therapeutic effect of photodynamic therapy are unknown [ 25 ]. Our results firstly identified that miR-32-5p was increased in PC tissues and cells, and was associated with the migration and invasion of PC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pheophorbide A, a product derived from the degradation of chlorophyll, has been used in the clinic as an imaging and anticancer agent [54,55,56,57,58,59]. Consequently, the ability of Pheophorbide A to treat RA has been evaluated [60].…”
Section: Photosensitizers Used To Treat Rheumatoid Arthritismentioning
confidence: 99%
“…miRNAs have been reported as oncogenes or tumor suppressor genes, which regulate tumorigenesis and metastasis through targeting various genes that are abnormally expressed in cancer cells (11). As a tumor suppressive miRNA, miR-145 has been reported to be decreased in numerous types of human cancer, including pancreatic cancer (12), prostate cancer (13), cervical cancer (14), gastric cancer (15), oral cancer (16), colorectal cancer (17), breast cancer (18), bladder cancer (19) and melanoma (20). These previous studies have indicated that miR-145 may suppress the growth, migration and invasion of cancer cells, and inhibit tumorigenesis by targeting various genes that are abnormally expressed in tumors.…”
Section: Introductionmentioning
confidence: 99%